Macular Microvasculature Is Associated With Total Cerebral Small Vessel Disease Burden in Recent Single Subcortical Infarction - Kwapong, William Robert; Jiang, Shuai; Yan, Yuying; Wan, Jincheng; Wu, Bo (Frontiers in Aging Neuroscience, 2022)
Purpose: To assess the retinal microvasculature, choriocapillaris, and choroidal thickness in recent single subcortical infarction (RSSI) patients compared with healthy controls. We also assessed the correlation between the macular microvascular changes and choroidal changes with their clinical implications in RSSI patients. Methods: Forty-six RSSI patients and 39 healthy controls were enrolled in our study. Magnetic resonance imaging (MRI) was done for all RSSI patients, and a total cerebral small vessel disease (CSVD) score was assessed for all patients. Swept-source optical coherence tomography (SS-OCT) was used to image and assess the choroidal thickness and SS-OCT angiography (SS-OCTA) was used to image and assess the macular microvasculature and choriocapillaris in all participants. Clinical information was collected for all participants. Results: RSSI patients showed significantly sparser inner retinal microvasculature (P = 0.003) when compared with healthy controls. RSSI patients showed significantly thinner choroidal thickness (P < 0.001) when compared with HC. No significant difference (P = 0.247) was seen when the choriocapillaris was compared between the two groups. CSVD burden (P = 0.014) and NIHSS score (P = 0.010) showed significant correlation with the inner retinal microvasculature of RSSI patients. The inner retinal microvasculature (P = 0.016) and choroidal thickness (P = 0.018) showed a significant correlation with the MoCA scores in RSSI patients. Conclusions: Our report suggests that retinal and choroidal imaging may serve as useful indicators to expand our understanding of RSSI and its clinical validity.